Analisis Marketing Politik Pasangan Fairid Naparin dan Umi Mastikah dalam Pemilihan Kepala Daerah di Kota Palangka Raya 2018 - Robbi Guntara; Ricky Zulfauzan; Anyualatha Haridison (Journal Ilmu Sosial, Politik dan Pemerintahan, 2021)
Political marketing is a marketing activity that aims to convey something to the public to know, understand the aims and objectives, trust, and accept and choose what the objectives of political marketing do. In this case in 2018 Palangkaraya City followed the local elections simultaneously in the election of mayor and deputy mayor won by the pair Fairid Naparin and Umi Mastikah. So with this, by analyzing the political marketing of couples Fairid Naparin and Umi Mastikah are things that need to be known to be understanding in terms of political marketing. This study uses descriptive research methods with a qualitative approach obtained based on the ability of researchers to connect the facts, data, and information obtained during the study. The objectives of this study are (1) Products, (2) Promotions, (3) Prices, and (4) Placements. The results of the research aim to convey something to the public in the form of products that are marketed based on partner's personal data, contain mature concepts, have a work program called vision and mission, promotion is the act of conveying to the public in such a way that suits the needs of the community, price not necessarily said in money, but how it has a price in the form of trust or confidence, and placement is an act that is carried out in the distribution or communication to the public. As a supporting factor for success in the presence of religion, family relationships, and age become the capital in determining political marketing to the voters to be delivered.